2015
DOI: 10.2134/agronj14.0431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low‐Cost Methods for Measuring Ammonia Volatilization

Abstract: Nitrogen fertilizer use to improve crop production is increasing worldwide, and subsequent N losses via NH 3 emissions generate undesirable economic and environmental consequences. Th us, low cost and practical methods to quantify NH 3 emissions are essential for the development of management practices that minimize environmental impacts. Th e objective of this study was to compare diff erent methods to quantify NH 3 loss following urea application to a grass fi eld and indoor soil boxes. Th e methods tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
(58 reference statements)
2
23
0
Order By: Relevance
“…As wind speed increases, the level of NH 3 measured by the dositube may be lower in the chamber due to increase air mixing. Shigaki and Dell (2015) also concluded that wind speed was a major factor impacting semi-open ammonia collection chamber readings. Table 4.…”
Section: Methods Assessmentmentioning
confidence: 99%
“…As wind speed increases, the level of NH 3 measured by the dositube may be lower in the chamber due to increase air mixing. Shigaki and Dell (2015) also concluded that wind speed was a major factor impacting semi-open ammonia collection chamber readings. Table 4.…”
Section: Methods Assessmentmentioning
confidence: 99%
“…However, semi‐static chambers are affordable (Grant et al, 1996), allowing the monitoring of different treatments in the same crop season, as they can be adapted to small flux‐footprint areas. In general, the accuracy is suitable for operational field applications (Shigaki and Dell, 2015), and they are used to compare NH 3 losses (AL) from different treatments, although it was found that they underestimated NH 3 emissions compared with the integrated horizontal flux method or the inverse dispersion method (Yang et al, 2017). …”
mentioning
confidence: 99%
“…For further methodological evaluations, NH 3 enrichment in the canopy environment of basil was determined by two additional methods: a) acid traps used as passive NH 3 samplers and b) calculation approach based on the NH 3 /NH 4 + equilibrium in the solution of the growing medium. The acid traps were made similar as described by Shigaki and Dell (2015) from plastic bowls (diameter: 10 cm) which were filled with 0.05 M H 2 SO 4 . To absorb atmospheric NH 3 , the traps were positioned for 24 h on the substrate surface ( Figure 2B).…”
Section: Aerial Nh 3 Measurements and Related Methodological Evaluationsmentioning
confidence: 99%